A Rare Case of Dengue Myocarditis: Challenges in Diagnosis and Management - Hafiz Muhammad Mubeen Nawaz; Rana Hanan; Muhammad Javed Ashraf (Shalamar Medical & Dental College, Lahore, Pakistan, 2024)
Dengue fever is a viral infection prevalent worldwide in tropical and subtropical regions and affects millions of people annually. It is associated with several complications, including rare yet significant cardiac complications, such as myocarditis. Myocarditis caused by dengue fever is challenging to diagnose and can be initially mistaken for acute coronary syndrome. This case report describes the diagnostic and management difficulties encountered by examining a young male patient who developed myocarditis as a complication of severe dengue fever. A 30-year-old male, a known smoker, presented to the emergency department with chest pain, diaphoresis, and hypotension. ECG indicated inferior wall ST-T changes. A physical examination revealed no abnormalities. The patient had a five-day history of fever and myalgia. The patient was initially diagnosed with acute coronary syndrome and cardiogenic shock. Primary coronary angiography revealed no abnormal findings. Echocardiography revealed a decreased LV ejection fraction of 40% and global wall hypokinesia with normal chamber dimensions, necessitating further investigation of the etiology. Subsequently, he was diagnosed with dengue virus-induced myocarditis based on laboratory investigations. This case underscores the rarity of dengue-associated myocarditis and emphasizes the pivotal role of maintaining a high clinical suspicion index for early diagnosis and management. Additionally, it emphasizes the significance of continuous case reporting to enhance our understanding and shape the evidence-based practices to address this uncommon complication.